Intemperance Use of the Internet with the University's Students (Journal of the College of Education for Women, 2019)
The research aims:1- To know the intemperance use of the internet by the University's students.2- To know the differences with a statistical indication in the intemperance use of the internet after the gender's inconstant ( Males-females).3- To know the differences with a statistical indication in the intemperance use of the internet after the Major's inconstant ( scientific- humanistic)This current research restricts a sample of the university students for both sexes.Theoretical frame:The research viewed several theories that explains intemperance use of the internet & the results.Research measures :1- Research has been adapted the scale ( Internet use) which was prepared by the Moroccan researcher ( Muhammad Muhammad Almaghribi) that measures intemperance ( Internet use) through the total grade that the examined get , the scale was adapted according to the